(untitled) (Interfaces: A Journal of Medieval European Literatures, 2024)
The paper analyses, edits and translates an unknown didactic poem on prosodic quantity attributed to John Tzetzes. The poem contains an autobiographical and personal component that has a lyrical dimension, challenging the way in which both didactic poetry and Byzantine poetry is traditionally understood. Moreover, manuscripts such as the one preserving the poem under investigation may be seen as sites for both the frozen moment of the didactic occasion and a continuation of the debate in the form of authorial comments on and to the scribe. Overall, the paper argues that didactic poetry in Byzantium was marked by improvisation and personal experience: in other words, a kind of occasionality.